SafeSearch: obfuscated VPN server using raspberry Pi for secure network / Mohd Faris Mohd Fuzi ... [et al.] - Mohd Fuzi, Mohd Faris; Mohd Alias, Mohamad Ridzuan; Kaur, Naginder; Abd Halim, Iman Hazwam (UiTM Cawangan Perlis, 2021)
Virtual Private Network (VPN) is a private network that uses public network to tunnel the connection from the users’ end to the VPN server. VPN allows users to create a secure connection to another network over the public Internet. VPNs can be used to shield users’ browsing activity and encrypts data transmitted over the network to prevent sniffing attack. Nowadays, users can either pay a premium price for a good VPN service or risk their privacy using free browser-based VPN. Thus, SafeSearch is developed to address these issues in mind. With SafeSearch, users will not need to fork out a lot of money for premium VPN subscription services or expose themselves to targeted advertising when utilising free browser-based VPN. In this study, open VPN protocol was used to create the VPN server on a microcomputer called Raspberry Pi. The software used was mostly open-source except for the VPN client. Obfuscation technique was used to hide VPN traffic by disguising it as just another normal Internet traffic against Deep Packet Inspection when passing through firewall. After the VPN server was established, tests were carried out to evaluate the functionality and reliability of the VPN server in “real-world” environment. The tests conducted were network restriction penetration assessment, network performance and user acceptance test. Penetration assessment result showed that SafeSearch is capable of bypassing web filtering and deep packet inspection. Network performance during SafeSearch connection has slight latency and bandwidth decline, although it is not overly affected. The outcome of the user acceptance test was positive as the majority of participants of the study were confident that SafeSearch can secure their connection and protect their privacy when browsing the web. To conclude, both objectives of this project were fully achieved and the scope of study was followed thoroughly.